Matematyka

Autorzy:Wojciech Babiański, Lech Chańko, Dorota Ponczek

Wydawnictwo:Nowa Era

Rok wydania:2015

Uzasadnij podane wyżej twierdzenie 4.54 gwiazdek na podstawie 13 opinii
  1. Liceum
  2. 1 Klasa
  3. Matematyka

Uzasadnij podane wyżej twierdzenie

4
 Zadanie

5
 Zadanie

6
 Zadanie
1
 Zadanie

`a)` 

`h^2+(1/2a)^2=a^2` 

`h^2+1/4a^2=a^2 \ \ \ |-1/4a^2` 

`h^2=3/4a^2` 

`h=sqrt(3/4a^2)=sqrt3/2a=(asqrt3)/2` 

 

 

`b)` 

`3a=24\ \ \ \ =>\ \ \ \ a=24:3=8` 

`h=(8sqrt3)/2=4sqrt3` 

 

 

`c)` 

`(asqrt3)/2=6\ \ \ |*2` 

`asqrt3=12\ \ \ \ |:sqrt3` 

`a=12/sqrt3=(12sqrt3)/3=4sqrt3` 

`O=3a=3*4sqrt3=12sqrt3` 

 

 

`d)` 

`r=1/3h=1/3*(asqrt3)/2=(asqrt3)/6` 

`P_(wp i sa n ego)=pi*r^2=pi*((asqrt3)/6)^2=` `pi*(a^2*3)/36=``pi/12a^2 ` 

 

`R=2/3h=2/3*(asqrt3)/2=` `(asqrt3)/3` 

`P_(op i sa n ego)=` `pi*R^2=pi*((asqrt3)/3)^2=` `pi*(a^2*3)/9=` `pi/3a^2` 

 

`P_(op i san e go)-P_(wp i san ego)=pi/3a^2-pi/12a^2=(4pi)/12a^2-pi/12a^2=(3pi)/12a^2=pi/4a^2`